MXenes as emerging materials to repair electroactive tissues and organs - Keshav Narayan Alagarsamy; Leena Regi Saleth; Saravanan Sekaran; Laura Fusco; Lucia Gemma Delogu; Maksym Pogorielov; Açelya Yilmazer; Sanjiv Dhingra (Bioactive Materials)
Nanomaterials with electroactive properties have taken a big leap for tissue repair and regeneration due to their unique physiochemical properties and biocompatibility. MXenes, an emerging class of electroactive materials have generated considerable interest for their biomedical applications from bench to bedside. Recently, the application of these two-dimensional wonder materials have been extensively investigated in the areas of biosensors, bioimaging and repair of electroactive organs, owing to their outstanding electromechanical properties, photothermal capabilities, hydrophilicity, and flexibility. The currently available data reports that there is significant potential to employ MXene nanomaterials for repair, regeneration and functioning of electroactive tissues and organs such as brain, spinal cord, heart, bone, skeletal muscle and skin. The current review is the first report that compiles the most recent advances in the application of MXenes in bioelectronics and the development of biomimetic scaffolds for repair, regeneration and functioning of electroactive tissues and organs including heart, nervous system, skin, bone and skeletal muscle. The content in this article focuses on unique features of MXenes, synthesis process, with emphasis on MXene-based electroactive tissue engineering constructs, biosensors and wearable biointerfaces. Additionally, a section on the future of MXenes is presented with a focus on the clinical applications of MXenes.